Usage pattern monitoring based on battery levels for standalone residential system - Lateef. O. Adewale, Oyinkanola; Hamid Bin Md Ali, Sawal; Ademola, Akande (International Journal of Engineering and Technology, 2019)
Non-availability of constant electricity with the reduction of energy consumption has become important issues for many people, especially those living in areas where there is a problem of electricity. True consumption and timely feedback are essential to support those who want to adjust their behavior in order to conserve energy. In this work, we proposed an interactive system that provides information on the state of the batteries, energy usage pattern in the house and schedule control so that there will be all round electricity rather than occasional blackout. Monitoring and control sensors for stand-alone power generation and control unit are based on three things: electrical consumption data from selected appliances, the time of usage i.e. priority of the appliance and the level of the battery at a particular time. This system will assist to encouragement in the use of renewable energy, especially those that use batteries as their backups such as window solar energy. Also, by self-monitoring for battery level will prolong the time of the system and will save the battery from the high depth of discharge in order to prevent the critical point of no return. Finally, the system can identify the highest consumption appliances and how to minimize the use of such on the battery for renewable energy.Â Â